Perbandingan Lama Hari Rawat Terapi Non Spesialis dan Spesialis Keperawatan pada Pasien Gangguan Jiwa (Journal of Telenursing (JOTING), 2025)
This study aims to compare the length of stay of mental disorder patients who receive non-specialist and specialist therapy at RSJMM. The method used is quantitative with a comparative method. The results showed that the length of stay of specialist therapy patients was 16.03 ± 2.945 days, with a median of 17 days, the shortest length of stay was 3 days, and the most extended length of stay was 21 days. The length of stay of non-specialist patients was 16.98 ± 2.81 days, with a median of 17 days; the shortest length of stay was 6 days, and the most extended length of stay was 28 days. The Mann-Whitney test (p of 0.015